C-reactive protein : albumin ratio in patients with resectable intrahepatic cholangiocarcinoma. Issue 6 (21st September 2020) - Matsumoto, T; Itoh, S; Yoshizumi, T; Kurihara, T; Yoshiya, S; Mano, Y; Takeishi, K; Harada, N; Ikegami, T; Soejima, Y; Baba, H; Mori, M
Abstract: Background: The C-reactive protein : albumin ratio (CAR) has been reported as a novel prognostic marker in several cancers. The aim of this study was to investigate the prognostic value of CAR in patients with intrahepatic cholangiocarcinoma (ICC). Methods: This was a single-centre retrospective study of patients who underwent surgery for ICC in a university hospital in Japan between 1998 and 2018. CAR, Glasgow Prognostic Score (GPS) and modified GPS (mGPS) were calculated. Their correlation with recurrence-free survival (RFS) and overall survival (OS) was analysed with Cox proportional hazards models. Results: Seventy-two patients were included in the study. Patients were divided into two groups according to the optimal CAR cut-off value of 0·02. CAR above 0·02 was associated with higher carbohydrate antigen 19-9 levels (20·5 versus 66·1 units/ml for CAR of 0·02 or less; P = 0·002), larger tumour size (3·2 versus 4·4 cm respectively; P = 0·031) and a higher rate of microvascular invasion (9 of 28 versus 25 of 44; P = 0·041). RFS and OS were shorter in patients with CAR above 0·02: hazard ratio (HR) 4·31 (95 per cent c.i. 2·02 to 10·63) and HR 4·80 (1·85 to 16·40) respectively. In multivariable analysis CAR above 0·02 was an independent prognostic factor of RFS (HR 3·29 (1·33 to 8·12); P < 0·001), but not OS. Conclusions: CAR was associated with prognosis in patients who had hepatic resection for ICC. Graphical Abstract: This study showed that a high C-reactive protein : albumin ratio (CAR) is an independent predictor of poor recurrence-free survival in patients with intrahepatic cholangiocarcinoma (ICC). The results also suggest that patients with ICC with a high CAR had a more aggressive tumour behaviour, including a larger tumour size, higher frequency of microvascular invasion and higher serum CA19-9 concentration, than those with a low preoperative CAR. High CAR associated with poorer survival=E2=80=99